Sorghum honeydew (Sphacelia sorghi McRae) control on sorghum (Sorghum bicolor (L) Moench), using commercial fungicides. - Mena, Héctor; Fuenmayor, Francia; Tejera, José; Jiménez, Rafael; Georges, Eudis (Agronomía Mesoamericana, 2006)
The experiment was conducted in Centro Nacional de Investigaciones in Maracay, Aragua, Venezuela. The goal of this job was determining the efficacy of some fungicides in controlling sorghum honeydew (Sphacelia sorghi McRae). A completely block randomized with four replications was used. Three systemic triazol fungicides were used and two non triazoles were included. Each dose was subdivided in three applications: 1/4 applied at panicle pre-emergence, 1/2 applied at 50 % flowering time and 1/4 applied at postflowering time, in order to cover the whole flowering period. The variables were: incidence or infected panicles per plot, panicle infection and the total infection/ plot. According to the results there was an overall good fungicide control. There was a group constituted by Tilt and Propizole, which gave the best fungus control with 96.96 and 96.55% of effectivity in controlling of panicles’ infection and a second group was integrated by Anvil, Benlate and Plantvax which made adequate control with no significant differences among them. In conclusion, the best fungicides were Tilt and Propizole. Benlate and Plantvax gave an adequate control but they are recommended under low inoculum pressure in order to avoid resistence and for economic reasons. Anvil showed 90.43% control; however, this fungicide has low relative efficacy when it is compared with other triazol fungicides.